2009
DOI: 10.1029/2008ja013931
|View full text |Cite
|
Sign up to set email alerts
|

Brightening of 630.0 nm equatorial spread‐F airglow depletions

Abstract: [1] Observations from the Boston University all-sky imaging system at Arecibo, Puerto Rico (18.3°N, 66.7°W, 28°N mag), show an unusual behavior of nighttime 630.0-nm airglow depletions. Associated with equatorial spread-F (ESF), these structures move eastward before reversing their motion and become airglow enhancements. Few other cases have been found, all during December solstices. For the case study presented here, data from the Arecibo incoherent scatter radar and the Republic of China Scientific Satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 29 publications
11
68
1
Order By: Relevance
“…In a related example, we found that a meridional wind can act in such a way that a density enhancement (relative to the nearby background) occurs within an ESF plume and that this enhancement has ion-velocity profiles similar to those observed (Le et al, 2003;Yokoyama et al, 2007). In fact this same SAMI3/ESF study reproduced an observed ESF airglow phenomenon, ESF airglow enhancement, which is related to the above-mentioned ESF density enhancement Martinis et al, 2009). In more recent simulations, which we report below, we find that ESF density enhancements can occur in the absence of winds if the ESF plumes are growing relatively slowly.…”
Section: Because the Strong Electronsupporting
confidence: 74%
See 4 more Smart Citations
“…In a related example, we found that a meridional wind can act in such a way that a density enhancement (relative to the nearby background) occurs within an ESF plume and that this enhancement has ion-velocity profiles similar to those observed (Le et al, 2003;Yokoyama et al, 2007). In fact this same SAMI3/ESF study reproduced an observed ESF airglow phenomenon, ESF airglow enhancement, which is related to the above-mentioned ESF density enhancement Martinis et al, 2009). In more recent simulations, which we report below, we find that ESF density enhancements can occur in the absence of winds if the ESF plumes are growing relatively slowly.…”
Section: Because the Strong Electronsupporting
confidence: 74%
“…This figure shows plots of log 10 n e , field-aligned O + velocity, vertical E × B velocity, and magnetic latitude versus longitude along a trajectory at fixed altitude 608 km. The top panel shows density increases similar to those seen in satellite data Le et al, 2003;Yokoyama et al, 2007;Park et al, 2008b;Martinis et al, 2009). We see that the E ×B drifts are everywhere upward and that the field aligned flows are everywhere poleward.…”
Section: Density Enhancements Associated With Weakly Growing Esfsupporting
confidence: 51%
See 3 more Smart Citations